P-242 Correction of IL10R Deficiency by Gene Therapy in Hematopoietic Stem Cells Leads to Amelioration of Colitis in Mice. (February 2017) - Frei, Sandra; Brendel, Christian; McCabe, Amanda; Shouval, Dror; Goettel, Jeremy; Williams, David; Snapper, Scott
Abstract : Background: IL10R deficiency in mice is associated with severe colitis and loss-of-function mutations in the interleukin-10 receptor (IL10R) lead to severe infantile inflammatory bowel disease (IBD). Patients typically present with serious colitis during infancy, which is often accompanied by perianal disease, folliculitis and/or joint inflammation. Affected children frequently do not respond to conventional therapies used to treat IBD. Remarkably, hematopoietic stem cell transplantation leads to sustained remission. However, it can be difficult to find a suitable HLA-matched donor. Here, we investigate gene correction strategies by gene therapy as an alternative treatment option to prevent colitis mediated by IL10R deficiency in mice. Methods: Il10rb−/− mice on the 129SvEv background were lethally irradiated and transplanted retroorbitally with lineage-depleted wild-type (wt) hematopoietic stem and progenitor cells (HSPCs), Il10rb−/− mock-transduced HSPCs or Il10rb−/− gene-corrected HSPCs employing lentiviral vectors expressing either GFP or Venus (n = 5 each group). Mice were monitored for signs of colitis based on clinical and endoscopic parameters, and were euthanized after 5 weeks. Colonic sections were collected for H&E staining. Histology score was determined based on crypt hyperplasia, inflammation, bowel wall thickening and crypt abscess. Analyses of immune phenotype and restoration of IL10 signaling and mature cell lineages were assessed by flow cytometry. Results: Mice that received wt or gene-corrected HSPCs had similar weight development while mock recipients showed a significant weight loss ( P < 0.0001). Colonoscopy revealed no or only mild signs of inflammation for wt and gene-corrected HSPC recipients while mock recipients showed severe signs of colitis. Histology scores were higher for mock (6.3 ± 0.9) recipients compared to wt (1.9 ± 1.1) or gene-corrected (4.6 ± 1.5) HSPC recipients. Overall, mock recipients expressed higher frequencies of IL17A +, TNF + and IFNg + CD4 + cells in the lamina propria, spleen and mesenteric lymph nodes compared to wt or gene-corrected HSPC recipients. No differences were observed for Tregs or pro- and anti-inflammatory macrophages subsets in the intestine. Mock recipients had higher numbers of neutrophils in the bone marrow, peripheral blood and spleen ( P < 0.01) compared to wt and gene-corrected HSPC recipients. Interestingly, mock recipients had significantly lower numbers of T and B cells in the bone marrow, peripheral blood and spleen compared to wt and gene-corrected HSPC recipients. IL10 signaling was successfully restored in monocytes, macrophages and T cells in gene-corrected HSPC, but not in mock recipients. Conclusions: Our data demonstrate that hematopoietic stem cell IL10R gene therapy can ameliorate/prevent colitis in IL10R deficiency in mice and support the development of this approach as an alternative treatment option for patients harboring loss-of-function mutations in the IL10R.